Ecosystem health:: from ecological unconsciousness to a new civilizatory project - Freire Vieira, Paulo; Favrim Gasparini, Marina (Sustainability in Debate, 2018)
This article presents a discussion in the field of ecosystem health approaches that considers both the new discoveries concerning the Anthropocene Era and the shortcomings of the current sustainable development model. It is argued that a transdisciplinary-oriented ecosystem health concept should be coupled with a constructivist, co-evolving view of “human-beings-in-ecosystems” in contemporary environmental research. Such a perspective sets up a radical break with the epistemological Cartesian tradition. In this sense, the authors suggest that the main challenge to be tackled is the overcoming of the dualistic belief systems hegemonic in western culture. In addition, they assume that this move remains in tune with the search for an alternative civilizing project.